1999
DOI: 10.1677/joe.0.1610069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on intraovarian nitric oxide production in the prepubertal rat

Abstract: Nitric oxide (NO) has been shown to contribute to ovarian development and function. In non-ovarian tissues NO can be altered by ethanol (ETOH), a drug considered to be a gonadal toxin in men as well as male and female rats. The present study was undertaken to determine if some of the detrimental effects of chronic ETOH exposure on prepubertal ovarian function could be due to ETOH-induced alterations in the intraovarian NO system. Rats were implanted with intragastric cannulae on day 24 and began receiving cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
(11 reference statements)
3
12
2
1
Order By: Relevance
“…Furthermore, inhibition of NOS in rats blocked the development of rapid tolerance to the motor-incoordinating effect of ethanol (Khanna et al, 1993(Khanna et al, , 1995 and alleviated the signs of ethanol withdrawal (Uzbay et al, 1997); this suggests that ethanol may act by inhibiting NOS-dependent pathways in these systems, possibly at the level of NOS. Although opposite results in experimental animals have been published (Fitzgerald et al, 1995;Ikeda et al, 1999;Naassila et al, 1997;Shi et al, 1998;Srivastava et al, 1999), our results demonstrate that ethanol has an inhibitory action on nNOS pathways in nerve cell cultures. In SH-SY5Y cells, inhibition of nNOS for 2 days with the selective nNOS inhibitor PLA caused a significant increase in the number of mAChRs.…”
Section: Figcontrasting
confidence: 80%
“…Furthermore, inhibition of NOS in rats blocked the development of rapid tolerance to the motor-incoordinating effect of ethanol (Khanna et al, 1993(Khanna et al, , 1995 and alleviated the signs of ethanol withdrawal (Uzbay et al, 1997); this suggests that ethanol may act by inhibiting NOS-dependent pathways in these systems, possibly at the level of NOS. Although opposite results in experimental animals have been published (Fitzgerald et al, 1995;Ikeda et al, 1999;Naassila et al, 1997;Shi et al, 1998;Srivastava et al, 1999), our results demonstrate that ethanol has an inhibitory action on nNOS pathways in nerve cell cultures. In SH-SY5Y cells, inhibition of nNOS for 2 days with the selective nNOS inhibitor PLA caused a significant increase in the number of mAChRs.…”
Section: Figcontrasting
confidence: 80%
“…As NO may be involved in ovulation (Shukovski & Tsafriri 1995, Bonello et al 1996, Yamauchi et al 1997) and differentiation of the granulosa cells (Hattori et al 1996, Nishida et al 2000, it is reasonable to propose that expression of eNOS mRNA preceded maximal expression of LH receptor mRNA in cultured granulosa cells. eNOS has been considered to be a constitutively expressed protein, but there are many reports of regulation of the expression of its gene , Bryant et al 1995, Van Voorhis et al 1995, Arnet et al 1996, JablonkaShariff & Olson 1997, El Dwairi et al 1998, Vega et al 1998, Hangai et al 1999, Srivastava et al 1999, Venkov et al 1999. In post-ischaemic rat retina, eNOS mRNA increased to a peak at 12 h, and decreased progressively beyond 24 h (Hangai et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…iNOS is transcriptionally regulated, whereas nNOS and eNOS are considered to be constitutively expressed. However, evidence accumulated in recent years indicates that these two isoforms are also subject to expressional regulation , Van Voorhis et al 1995, Bryant et al 1995, Arnet et al 1996, Jablonka-Shariff & Olson 1997, Vega et al 1998, El Dwairi et al 1998, Srivastava et al 1999, Hangai et al 1999, Venkov et al 1999. Changes in their expression may have physiological and pathophysiological consequences.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that ethanol induced a rapid increase of ecNOS protein and mRNA expression levels and activity [44][45][46][47][48]. Ethanol modulates tyrosine kinase activity [49], and tyrosine kinase regulates expression of ecNOS via posttranscriptional mechanisms [50,51].…”
Section: Discussionmentioning
confidence: 99%